Aerodynamic optimization of a Darrieus-Savonius wind turbine with guide vane for power generation in the coastal area of Pacitan Regency - Yoga Arob Wicaksono; Ahmad Arbi Trihatmojo; Musyaddad Nurwahyono; Muhammad Halim (TURBO [Tulisan Riset Berbasis Online], 2026)
The Darrieus–Savonius wind turbine has significant potential for application in the coastal area of Pacitan Regency, Indonesia, as it combines the high efficiency of the Darrieus rotor with the superior self-starting capability of the Savonius rotor. Although the use of guide vanes has been widely investigated in vertical-axis wind turbines, studies examining the influence of the number of guide vanes on the flow characteristics and aerodynamic performance of Darrieus–Savonius wind turbines remain limited. This study investigates the effects of three guide vane configurations (3, 4, and 5 vanes) using Computational Fluid Dynamics (CFD) simulations performed in OpenFOAM. The simulations were conducted at a free-stream wind speed of 10 m/s and a rotor angular velocity of 5 rad/s. Turbine performance was evaluated in terms of the torque coefficient (CT) and power coefficient (CP), while the flow characteristics were analyzed through velocity and pressure distributions around the rotor. The results indicate that the 4-guide-vane configuration achieved the best performance, yielding a CT of 0.35 and a CP of 0.175, which were higher than those obtained with the 3-guide-vane configuration (CT = 0.33, CP = 0.165) and the 5-guide-vane configuration (CT = 0.29, CP = 0.145). This configuration effectively directed the incoming airflow toward the rotor, resulting in a greater pressure difference across the blades. In contrast, the 5-guide-vane configuration induced blockage and increased turbulence, leading to a reduction in turbine performance. These findings demonstrate that the 4-guide-vane configuration is the most effective design for enhancing the aerodynamic performance of Darrieus–Savonius wind turbines. Keywords: Small-scale wind turbine; Darrieus–Savonius; Guide vanes; Computational Fluid Dynamics (CFD); Power and torque coefficients